PENGARUH MANAJEMEN LABA, UKURAN DEWAN KOMISARIS, KEPEMILIKAN INSTITUSIONAL, DAN KUALITAS AUDIT TERHADAP BIAYA MODAL PERUSAHAAN - Andriana, Denny; Friska, Renny (Jurnal Riset Akuntansi dan Keuangan, 2014)
This research aims to determine the effect of earnings management, board of commissioners size, institutional ownership, and quality audits of the cost of capital for Badan Usaha Milik Negara (BUMN) in the period 2010-2012. Purposive sampling method used in determining the sample resulted in 23 of 141 observations were carried out on state-owned enterprises listed on BUMN for the period 2010-2012. The data analysis technique used in this research is multiple regression. The test results indicate that earnings management and institutional ownership partially negatively affect the cost of capital. The test results indicate that earnings management and institutional ownership partially negatively affect the cost of capital.